Criminal Investigation Polres Kudus Unit Efforts In The Prevention Of The Corruption In Village Funds Management - Luk Har Syan’in; Gunarto Gunarto; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Interest and research efforts is to know the Kudus Police Criminal Investigation Unit of the Prevention of Corruption Within the Village Fund Management.Corruption as a criminal act detrimental to state finance, society and individuals, classified as white collar crime is the main enemy of the Indonesian people in addition to narcotics and terrorism. Combating corruption not only through law enforcement (repression) but preventive measures should be preferred. Village Fund aims to promote the welfare of rural communities through its programs, so that should be the prevention of irregularities in utilization as well as in the village in the village Karangmalang, District Gebog, KudusUnderstanding of research results Karangmalang village residents, still very little about corruption, as well as the importance of the role of citizens in preventing corruption adi trans particularly as regards management of village funds. There are some obstacles and constraints encountered in reality on the ground by the Society and the Village Padurenan, District Gebog, Kudus Regency in respect of the management of village funds, and in particular as prevention of corruption use village funds, but the fund management nice village, transparent, and accountable in accordance with the statutory provisions of supported community participation oversee and report slogans, as one prevention of corruption to increase the effectiveness fitas development and welfare of rural communities in the vicinity.Keywords: Prevention of Corruption Act; Village Fund.